BILAYER TABLET TENDERED IMMEDIATE RELEASE OF PARACETAMOL AND SUSTAINED RELEASE OF IBUPROFEN FOR QUICK ONSET OF ACTION AGAINST PAIN AND FEVER - DEVENDER CHAUHAN; DINESH KAUSHIK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this research was to formulate bi-layer tablet which contains immediate-release layer of Paracetamol for quick onset of action and sustained release of Ibuprofen for prolonging long period. Materials and Methods: The following chemicals were used: Paracetamol (Combiotic Global Pvt. Ltd., India), Ibuprofen (Combiotic Global Pvt. Ltd., India), microcrystalline cellulose (MCC) (Avicel), and Polyvinylpyrrolidone (PVP) K-30 (Loba Chem). Wet granulation method was adapted to formulate the bilayer tablets. The immediate-release layer of Paracetamol was prepared using sodium starch glycolate as superdisintegrants, MCC as diluent, starch as binder. The sustained release layer of Ibuprofen was prepared using high-performance liquid chromatography E50LV and ethyl cellulose as binder along with other excipients such as MCC, PVP, and magnesium stearate by wet granulation technique. Result and Discussion: The release rate of Paracetamol from Formulations 1 was more than 80% at 40 min. In case of Ibuprofen, sustained-release polymers such as HPMC E50 LV were used to increase the release time. Conclusion: The bilayer tablets were prepared and show good release rate.